Motivation, Intention and Opportunity: Wearing Masks and the Spread of COVID-19 - Geoff Kaine; Vic Wright (COVID, 2023)
Prior to the emergence of the Omicron variant, we found large regional differences (ƞ2 = 0.19) in the frequency of wearing face masks in New Zealand even though the strength of people’s motivation to wear face masks to prevent the spread of COVID-19 was similar across regions. These differences were associated with regional differences (as measured by case numbers) in the risk of COVID-19 infection. The emergence of Omicron and its spread throughout New Zealand in conjunction with the cessation of lockdowns offered the opportunity to test whether regional differences in the frequency of mask wearing disappeared once the risk of COVID-19 infection became uniform across the country. It also created an opportunity to investigate differences in people’s behaviour with respect to wearing masks in private and in public. The results confirmed that regional differences in the frequency of mask wearing disappeared once Omicron spread through the country. We also found that the frequency of wearing masks was significantly lower when with family or friends than when out in public.